As Pérfidas salomés : o tema do amor na estética simbolista e as novas formas de amar na Belle époque carioca – Fon-Fon ! e Para Todos... (1900-1930) - Cláudia de Oliveira (Centre de Recherches sur les Mondes Américains, 2007)
As Pérfidas salomés (Perfidious salomés) analyses a modern representation of the feminine, using the biblical myth as a reference to invite reflection upon the new female sexuality as presented in the Brazilian illustrated magazines, Fon-Fon ! and Para Todos…, both of which were edited by a group of intellectuals from the symbolist literary tradition in Rio de Janeiro in the first three decades of the 20th-century.